(untitled) (Indian Journal of Integrative Medicine, 2024)
Background: The integration of formative assessment, specifically Direct Observation of Procedural Skills (DOPS), in homeopathic education is an emerging tool for assessment of students of homoeopathy which has been amended by national commission of homoeopathy (NCH) in 2020. Formative assessment plays a crucial role in the continuous evaluation of students’ understanding and practical skills in the complex field of homeopathy. Aim & Objective: The study focuses on the application of DOPS within the frameworks of Bloom’s Taxonomy and Miller’s Pyramid, emphasizing its role in fostering well-rounded homeopathic pharmacy learning objective compared with traditional methods. Method: Ninety-four first-year BHMS students participated in a study involving a practical experiment on Thuja occidentalis. DOPS was employed as a formative assessment tool, evaluated by trained assessors. Pre-tests and post-tests were conducted to assess theoretical knowledge and practical application. Data analysis included mean and standard deviation calculations, qualitative analysis of DOPS assessments, and ethical considerations were adhered to. Result: The DOPS assessments revealed improvements in students’ understanding, preparation, and interpretation skills. Mean scores for specific skills showed enhancement, with slight variations. The moisture content experiment demonstrated an increase in mean values between the first and second DOPS, suggesting improved consistency in estimation. Standard deviations indicated reduced variability in the second DOPS, reflecting enhanced precision. Discussion: The discussion interprets the findings, emphasizing the positive trajectory observed in students’ procedural skills and theoretical knowledge. Detailed analysis of specific DOPS skills and quantitative results from the moisture content experiment highlight areas of improvement and stability. Recommendations for continued emphasis on technical ability and communication skills are made. Conclusion: The study concludes that the integration of DOPS in assessing procedural skills for estimating moisture content in Thuja occidentalis positively influences the development of first-year homeopathic students. The findings support the effectiveness of formative assessment in enhancing various dimensions of students’ competence. Recommendations for ongoing efforts in specific skill areas aim to further support students in their journey toward becoming proficient homeopathic practitioners.